ANALISIS KINERJA KEUANGAN UNIT PENGELOLA KEUANGAN (UPK) DESA MONTONG ARE DITINJAU DARI RASIO PROFITABILITAS TAHUN 2015-2020 - Saepul Pahmi (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the financial performance of the Montong Are Village Financial Management Unit (UPK) using the profitability ratio measurement tool. This research is expected to provide an overview of the ability of the Montong Are Village UPK to manage resources to generate good profits. This research was conducted at the Montong Are Village Financial Management Unit (UPK) which is engaged in the distribution of revolving loan funds. The research method used in this study is a descriptive method, namely by describing the profitability ratios and then comparing them with the standard financial ratios. The results of this study indicate that for five years from 2015-2020 the results of the calculation of financial ratios show fluctuating values, both ROA, ROE, NPM, and GPM ratios. The ROA ratio shows the lowest figure of 4% and the highest of 11%. Likewise with ROE where the lowest ratio figure is 5% and the highest is 12%. Meanwhile, the lowest GPM and NPM ratios are 15% and 6% respectively and the highest is 28% and 15%.